2021
DOI: 10.3897/aiep.51.63281
|View full text |Cite
|
Sign up to set email alerts
|

A nitrogen factor for European pike-perch (Sander lucioperca), northern pike (Esox lucius), and sheatfish (Silurus glanis) fillets

Abstract: Measures for consumer protection against food adulteration and misleading labeling are integrated into EU legislation, including methods for detection of misleading practices. Verification of meat content is available for marine products but not for freshwater fish because of the lack of standard nitrogen factors. The aim of this study was to establish nitrogen factors for European pike-perch Sander lucioperca (Linnaeus, 1758), northern pike Esox lucius Linnaeus, 1758, and sheatfish Silurus glanis Linnaeus, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…In our study, flash moisture ranged between 77.68 ± 0.45% and 79.45 ± 0.37% in relation to feeding type. Close values for the same trait were reported by other authors [15,16,55].…”
Section: Qualitative Flesh Productionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, flash moisture ranged between 77.68 ± 0.45% and 79.45 ± 0.37% in relation to feeding type. Close values for the same trait were reported by other authors [15,16,55].…”
Section: Qualitative Flesh Productionsupporting
confidence: 88%
“…There were also observed fluctuations due to the activity of alteration microorganisms as well as oxidative processes that appeared on the sample surface [64,69,72]. Moreover, for the case of lipids, the literature indicates close values to those obtained in the current study [15,16]. Linhartova et al (2018) [73] indicated catfish flesh lipids contents of 4.13% in intensive rearing system samples and 2.97% in the semi-intensive system.…”
Section: Qualitative Flesh Productionsupporting
confidence: 76%
See 2 more Smart Citations
“…Suitable methods for determining the meat content in freshwater fish products are absent. The reason for this state is the absence of species-specific nitrogen content (nitrogen factor) for freshwater fish, except for the Nile mouthbreeder (Oreochromis niloticus) (CA 2004), common carp (Cyprinus carpio) (Honzlova et al 2021a), and European pikeperch (Sander lucioperca), northern pike (Esox lucius), and wels catfish (Silurus glanis) (Honzlova et al 2021b).…”
mentioning
confidence: 99%